The Application of the Murabaha Contract in Sharia Financing: A Sharia Economic Law Perspective - Rajindra, Rajindra; Syamsuddin, Syamsuddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This article examines the application of the Murabaha contract as one of the most widely used financing instruments in Islamic financial institutions. Through a normative juridical approach, the study analyzes the legal foundations, implementation mechanisms, and compliance of Murabaha practices with the principles of Sharia Economic Law. The discussion highlights key aspects such as transparency in cost disclosure, the requirement of asset ownership by the financing institution, and the prohibition of speculative or interest-based elements. The findings indicate that, when implemented according to established Sharia guidelines, the Murabaha contract serves as an effective, fair, and sharia-compliant financing model that supports economic activities while promoting ethical financial interactions. This study also identifies common challenges in practice, including issues of documentation, risk allocation, and deviations from ideal Sharia procedures, and offers recommendations for strengthening regulatory oversight and institutional governance.